0450 Effect of Lemborexant on Early Morning Awakening in Subjects with Severe Problems with Waking Too Early. (25th May 2022) - Moline, Margaret; Zee, Phyllis; Kumar, Dinesh; Pappadopulos, Elizabeth; Malhotra, Manoj
Abstract: Introduction: Lemborexant (LEM) is a dual orexin receptor antagonist approved in multiple countries for the treatment of adults with insomnia. In Study E2006-G000-304 (Study 304; NCT02783729), LEM improved sleep onset and sleep maintenance. This analysis evaluated treatment with LEM in subjects reporting "problems waking up too early" on the Insomnia Severity Index (ISI) Item-3 as assessed by wake after sleep onset in the second half of the night (WASO2H). Methods: Study 304 was a 1-month, randomized, double-blind, placebo(PBO)-controlled and active-comparator (zolpidem extended-release 6.25mg [ZOL]) study of LEM 5mg (LEM5) and LEM 10mg (LEM10). Subjects whose baseline scores were ≥3 (severe/very severe) for ISI Item-3 were included in this analysis. WASO2H was defined as minutes of wake during the interval from 240 minutes after lights off until lights on (based on 8hr time in bed). WASO2H was measured at Days 1/2 and 29/30 using polysomnography and averaged across consecutive nights; change from baseline was analyzed using mixed effect model repeated measurement analysis. Results: Treatment groups were (number of subjects: treated/had ISI Item-3 scores ≥3) LEM5 (220/140), LEM10 (219/140), ZOL (216/158) and PBO (180/122). Baseline mean (standard deviation) WASO2H (minutes) ranged from 77.8-82.25 (30.3-35.5) across treatment groups. By Day 1/2, WASO2H improved significantly with LEM versus ZOL and PBO. Least-squares mean (LSM; standard error [SE]) WASO2H change from baseline at Day 1/2 was -15.56(2.3) (PBO), -34.19(2.2) (LEM5), -42.54(2.2) (LEM10), and -27.82(2.1) (ZOL); all P<0.0001 versus PBO, P=0.0222 and P<0.0001 for LEM5 and LEM10 versus ZOL, respectively. Improvements in WASO2H were maintained through Day 29/30. LSM (SE) change from baseline in WASO2H at Day 29/30 was -15.07(2.5) (PBO), -30.06(2.4) (LEM5), -34.30(2.4) (LEM10), -25.30(2.3) (ZOL); all P<0.002 versus PBO, P=0.1187 and P=0.0033 for LEM5 and LEM10 versus ZOL, respectively. ISI Item-3 improved from ≥3 at baseline to <3 for most LEM5 (97/137[70.8%]) and LEM10 (92/133[69.2%]) treated subjects. Conclusion: LEM provided significant benefit in WASO2H versus PBO (LEM5 and LEM10) and versus ZOL (only LEM10 at Day 29/30) among subjects with severe/very severe problems with waking too early. Improvements reported for ISI Item-3 for LEM subjects supports this benefit. Support (If Any): Eisai Inc.